MODEL DINAMIK PERMINTAAN IMPOR KEDELAI DI INDONESIA - Ainul Dwi Pangestu; Aris Soelistyo (Jurnal Ilmu Ekonomi JIE, 2019)
This study aims to analyze the Dynamic Model of Soybean Import Demand in Indonesia so that it can be known simultaneously and partially, soybean import demand. This study aims to determine the effect of the real exchange rate, and GDP on Indonesian soybean imports from 1987 to 2017 for analyzing data, this study uses the multiple linear regression analysis of the Partial Adjustment Model (PAM) and time-series data. The results of this study indicate that the GDP variable has a positive and significant effect on the import value of Indonesian soybeans, where an increase of 1$ increases 0.39 while for the real positive and not significant exchange rate variable where if there in an increase of 1$, the import value will increase by 0.16. From the results of the regression, it is obtained that the R-square value is 87.68%. This illustrates that the independent variable was 87.68%, while 12.32% was explained by other variables outside the model